About the abstract-concrete danger crimes in the general doctrine of danger crimes - Rocha Silveira, Dana (2021)
Crimes of danger, unlike crimes of harm, currently consist of a dogmatic category responsible for provoking wide-ranging discussions in the criminal-legal area. In this sense, considering the general conjuncture in which they are inserted, as well as the discussions about their necessity and legitimacy, this article pursued the objective of promoting analysis of the dogmatic model of abstract-concrete danger crimes as a proposition of an effective and guaranteed instrument of criminal typification. For an efficient approach to the theme, the theory of legal good’s protection was adopted as a theoretical mark, besides the deductive and dialectical methods, using mainly the bibliographic research technique, combined with jurisprudential research. Concerning the results obtained, the verified conclusion is that the crimes of danger are indispensable to the Postmodern Society, as well as legitimate, provided they are based on minimal material reasoning. Furthermore, specifically regarding the abstract-concrete danger crimes, it was found that these constitute an autonomous and intermediate modality of danger, although still largely unexplored, requiring in-depth studies in the area, to enable their correct application.